Bronchoscopic intervention in the management of primary tracheobronchial adenoid cystic carcinoma with dyspnea - Wu, Xiuxiu; Qiu, Xiaojian; Jin, Beibei; Niu, Jinmu; Jin, Yankun; Bu, Xiaoning; Wang, Juan (Frontiers in Oncology, 2025)
BackgroundPrimary tracheobronchial adenoid cystic carcinoma (TACC) is a rare, slow-progressing malignant tumor whose airway obstruction frequently compromise survival. This study aimed to investigate the value of interventional bronchoscopy in TACC.MethodsWe retrospectively analyzed the clinical data of TACC patients treated between January 2006 and December 2024. 52 patients were stratified into two groups: the bronchoscopic intervention alone group (n = 25) and combined therapy group (n = 27). Kaplan-Meier methodology was employed to estimate median progression-free survival (PFS), overall survival (OS), and survival rates. Prognostic factors were further evaluated using Cox proportional hazards model.ResultsThe mean age of 52 TACC patients was 51.77 ± 14.40 years. Bronchoscopic intervention demonstrated significant reduction in mMRC score and Freitag grade (P < 0.01). Median PFS and OS were 20 months and 118 months, respectively. The 3-/5-/10-year OS were 80.00%, 69.12%, and 34.87%. The combined therapy group exhibited superior PFS compared to the bronchoscopic intervention alone group (P < 0.05). Cox analysis identified combined therapy and stenosis degree as independent prognostic factors for PFS (P < 0.05).ConclusionsBronchoscopic intervention demonstrated significant efficacy in alleviating dyspnea and airway stenosis while sustaining long-term survival in TACC patients. Multimodal therapy showed potential advantages in delaying disease progression.